Glioblastoma Primary Cells Retain the Most Copy Number Alterations That Predict Poor Survival in Glioma Patients - Chen, Chia-Hua; Lin, Ya-Jui; Lin, You-Yu; Lin, Chang-Hung; Feng, Li-Ying; Chang, Ian Yi-Feng; Wei, Kuo-Chen; Huang, Chiung-Yin (Frontiers in Oncology, 2021)
Gliomas are solid tumors that originate from glial cells in the brain or spine and account for 74.6% of malignant primary central nervous system tumors worldwide. As patient-derived primary cells are important tools for drug screening and new therapy development in glioma, we aim to understand the genomic similarity of the primary cells to their parental tumors by comparing their whole-genome copy number variations and expression profile of glioma clinicopathologic factors. We found that the primary cells from grade II/III gliomas lost most of the gene copy number alterations (CNAs), which were mainly located on chromosome 1p and 19q in their parental tumors. The glioblastoma (GBM) primary cells preserved 83.7% of the gene CNAs in the parental GBM tumors, including chromosome 7 gain and 10q loss. The CNA gains of LINC00226 and ADAM6 and the chromosome 16p11 loss were reconstituted in primary cells from both grade II/III gliomas and GBMs. Interestingly, we found these CNAs were correlated to overall survival (OS) in glioma patients using the Merged Cohort LGG and GBM dataset from cBioPortal. The gene CNAs preserved in glioma primary cells often predicted poor survival, whereas the gene CNAs lost in grade II/III primary cells were mainly associated to better prognosis in glioma patients. Glioma prognostic factors that predict better survival, such as IDH mutations and 1p/19q codeletion in grade II/III gliomas, were lost in their primary cells, whereas methylated MGMT promoters as well as TERT promoter mutations were preserved in GBM primary cells while lost in grade II/III primary cells. Our results suggest that GBM primary cells tend to preserve CNAs in their parental tumors, and these CNAs are correlated to poor OS and predict worse prognosis in glioma patients.